Sterigmatocystin biosynthesis in Aspergillus nidulans requires a novel type I polyketide synthase. - Yu, J H (1995)
A filamentous fungus, Aspergillus nidulans, produces the carcinogenic mycotoxin sterigmatocystin (ST), which is a polyketide-derived secondary metabolite. A gene (pksST) encoding the ST polyketide synthase (PKSst) in A. nidulans was cloned, sequenced, and characterized. Large induced deletion mutants, which did not make ST or any ST intermediates, were used to identify genes associated with ST biosynthesis. Among the transcripts detected within the deletion region, which showed developmental expression with ST production, was a 7.2-kb transcript. Functional inactivation of the gene encoding the 7.2-kb transcript blocked production of ST and all ST intermediate substrates but did not affect transcription of the pathway genes, indicating that this gene was involved in a very early step of ST biosynthesis. These results also indicate that PKSst was not associated with activation of other ST genes. Sequencing of the region spanning this gene revealed that it encoded a polypeptide with a deduced length of 2,181 amino acids that had high levels of similarity to many of the known polyketide synthases and FASs. This gene, pksST, encodes a multifunctional novel type I polyketide synthase which has as active sites a beta-ketoacyl acyl carrier protein synthase, an acyltransferase, duplicated acyl carrier proteins, and a thioesterase, all of these catalytic sites may be multiply used. In addition, a 1.9-kb transcript, which also showed developmental expression, was mapped adjacent to pksST, and the sequence of this gene revealed that it encoded a cytochrome P-450 monooxygenase-like peptide.